Narratives of resistance: femicide and artivist practices in focus - Marcondes, Amanda [UNESP] (Universidade do Estado de Santa Catarina, 2024)
This essay aims to analyze the case of femicide involving the cycling artist Julieta Hernández in January 2024, from a decolonial feminist perspective aligned with the field of expanded scene in Latin America. It emphasizes the relevance of feminist artivist practices as a means to create counter-narratives to gender violence processes stemming from the colonial/modern system (Segato, 2012). Finally, in light of the concept of liminal practices (Caballero, 2011), the essay explores the construction of performative acts that arise from a fractured social fabric, collectively aiming for the symbolic restoration of identities ruptured by it.
Narrativas de resistencia: feminicidio y prácticas artivistas en foco Resumen
Narrativas de resistência: feminicídio e práticas artivistas em foco
Keywords: Decolonial feminism; Femicide; Feminist artivism; Liminal practices